Characterization of Raw Kapok Fiber as Filtration Medium for Biodiesel Plant Waste Oil - Sanusi, Muhammad Syakir; Kasmin, Ashari; Hussin, Rosniza (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The study aims to examine the potential of kapok fiber as a filtration medium for biodiesel plant waste oil. Kapok fiber, derived from the Ceiba Pentandra tree, is a natural fiber with exceptional hydrophobic-oleophilic properties. This properties are attributed to its permeable hollow lumen structure and the presence of a waxy substance on its surface. The objective was to analyze the properties of Kapok fiber before and after its use as a filtration medium using Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FTIR), and Contact Angle measurements. The SEM study of the kapok fiber reveals a waxy surface, hollow lumen, and porous features that are considered to have significant oil storage capacity. The FTIR measurement indicates a prominent peak at 1741 cm⁻¹, which corresponds to the stretching vibrations of the C=O bond. This peak is characteristic of ester groups found in biodiesel waste oil. The contact angle measurements of raw kapok fiber, taken was 145.3°, exhibit a significant degree of hydrophobicity. But after filtering, the sample shows a contact angle of 0°, indicating complete wetting. There is a significant difference in filtration efficiency between the two flow directions. The efficiency of horizontal flow filters increases from 36.40% at a width of 20 mm to 49.20% at a width of 40 mm, and further to 61.95% at a width of 60 mm. Vertical flow filters exhibit superior efficiency at various widths: 64.10% at 20 mm, 70.40% at 40 mm, and 78.35% at 60 mm. The vertical flow filters exhibit greater filtration efficiency, indicating that they are more successful in capturing contaminants compared to horizontal flow filters. Lastly, kapok fiber proved to be and effective oil filtration medium.